Analysis of the Effectiveness of Health Warnings Oral Cancer Pictures on Cigarette Pack Pictures - Data Rizqueen Maipana; Fitri Pralistami; Putri Nabillah; Tasya Aulia Tamara (Pena Cendekia Insani, 2021)
Smoking behaviour has become a risk factor for many diseases. The government has made various efforts in reducing the number of smokers. One of them issued a policy of embedding pictorial health warnings on cigarette packs. This study aims to determine the effectiveness of pictorial smoking warnings on the desire to quit smoking. This study is a quantitative study with a cross-sectional research design using primary data. This research was conducted in Indonesia in January-August 2021. The research population is all Indonesian people who smoke and do not smoke. The research sample was 463 people. The sampling technique used was random sampling. The research instrument used a questionnaire, with data collection techniques using google form. Analysis of the data used is a univariate analysis to see the frequency distribution of each variable. The results showed that the respondents were afraid after seeing the pictorial health warnings on cigarette packs as many as 366 people (79%) with a strong desire to quit smoking as many as 311 people (67.2%). This means that pictorial health warnings on cigarette packs are more effective than written warnings. It is hoped that the government can enlarge the health warnings on cigarette packs to reduce the number of cigarette consumption in Indonesia